FFECT OF OCIMUM SANCTUM DRY LEAF POWDER ON IMMUNE RESPONSE IN BROILERS FED OCHRATOXIN - Nayak, Anju; Joseph, E; Nayak, S; Swamy, M; Baghel, RPS (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
A study was conducted to evaluate the immunomodulatory property of Ocimum Sanctum dry leaf powder in ochratoxin supplemented fed broilers. Day old, 108 broilers were distributed into nine groups in duplicate. Serum was collected on day 15th, 25th and 35th and humoral immunity in broilers towards New castle disease was measured. Significantly lower titer against NDV was observed in broilers receiving ochratoxin, on 15th, 25th and 35th day. Broilers receiving 4 g Ocimum Sanctum dry leaf powder / kg feed showed highest NDV titer followed by broilers receiving 2 g Ocimum Sanctum dry leaf powder / kg feed. Significantly (P
Keywords: Ocimum Sanctum; Humoral immunity; haemagglutination inhibition